Big audit firms as regulatory intermediaries in transnational labor governance. Issue 2 (4th October 2018) - Fransen, Luc; LeBaron, Genevieve
Abstract: Due diligence and corporate disclosure initiatives effectively expand the role of professional service firms as regulatory intermediaries in the governance of conditions of production in global supply chains. In this paper, we examine the rise of the "Big Four" audit firms in the market for services connected to transnational labor governance. Through a qualitative case study of audit firms in modern slavery governance, we argue that the Big Four's political repertoire for transnational labor governance expands beyond the roles that are typically linked to their services, and promotes an agenda that touches on key debates on what constitutes proper transnational labor governance. Big audit firms engage in a variety of informal and covert influencing practices and are shown to promote an agenda of incrementalist soft‐law labor governance, opposing concrete performance targets, binding public regulation and an independent watchdog role for civil society.